From mean and median income to the most adequateway of taking inequality into account - Kreinovich V. (Springer Verlag, 2015)
© Springer International Publishing Switzerland 2015. How can we compare the incomes of two different countries or regions? At first glance, it is sufficient to compare the mean incomes, but this is known to be not a very adequate comparison: according to this criterion, a very poor country with a few super-rich people may appear to be in good economic shape. A more adequate description of economy is the median income. However, the median is also not always fully adequate: e.g., raising the income of very poor people clearly improves the overall economy but does not change the median. In this paper, we use known techniques from group decision making—namely, Nash’s bargaining solution—to come up with the most adequate measure of “average” income: geometric mean. On several examples, we illustrate how this measure works.